Safe Motherhood Practices of Women in Urban and Rural Areas of Chitwan District, Nepal - Koirala, Sushila (Marsyangdi Journal, 2021)
Safe motherhood practices ensure all women receive the care they need to be safe and healthy throughout pregnancy and childbirth. It is one of the most important pillars for preventing maternal morbidity and mortality. A descriptive comparative study was conducted to compare the safe motherhood practices in selected VDC and Municipality of Chitwan District. The purposive sampling method was applied in which 120 respondents were married and had at least one child. Among them, 59 respondents were from Bharatpur Municipality and 61 respondents from Mangalpur VDC. Data was collected by interviewing mothers using a structured interview schedule. Descriptive statistics were used for data analysis. The results showed that the number of mothers in the rural area practicing safe motherhood is lower than the number of mothers in the urban area. The number of ANC visits/PNC visits, use of Iron tab, institutional delivery and use of extra nutritious diet or meal per day during pregnancy and after pregnancy were higher in respondents of the urban area. The main reason for not taking ANC/PNC services during their last birth was lack of knowledge and second was their poor economic conditions. This study concludes that the trend of visiting ANC services, delivery care, and PNC services properly are high in the age group 20-39 years and it is increasing with their level of education. Special awareness programmes about information regarding safe motherhood practices should be planned and launched especially targeting the women of rural areas.